Physical inactivity during leisure and school time is associated with the presence of common mental disorders in adolescence - Vanessa Roriz Ferreira; Thiago Veiga Jardim; Thaís Inácio Rolim Póvoa; Ricardo Borges Viana; Ana Luiza Lima Sousa; Paulo César Veiga Jardim
ABSTRACT OBJECTIVE: To investigate the association of physical inactivity in leisure and school time with common mental disorders during adolescence. METHODS: The sample consisted of 73,399 adolescents (12-17 years old), participants in the Estudo de Riscos Cardiovasculares em Adolescentes (Erica - Study of Cardiovascular Risks in Adolescents). This cross-sectional, national and school-based study was conducted in 2013 and 2014 in Brazilian municipalities with more than 100,000 inhabitants. Leisure time physical activity was categorized according to weekly practice volume, and adolescents were classified as active (≥ 300 minutes/week), inactive (0 minute/week) and insufficiently active (1-299 minutes/week). Sports practice and participation in physical education classes at school were also analyzed. The presence of common mental disorders was assessed based on the general health questionnaire, with a cutoff point greater than or equal to 3. Odds ratios (OR) were estimated using multiple logistic regression. RESULTS: The chance of common mental disorders was 16% higher in the group that reported being inactive (0 minute/week) at leisure time (OR = 1.16; 95%CI 1.06 (1.27). The prevalence of common mental disorders was higher among young people who did not practice sports (37.2% vs. 25.9%; OR = 1.14; 95%CI 1.04-1.25) and did not participate in physical education classes at school (39.5% vs. 29.6%; OR = 1.25; 95%CI 1.15-1.36). Insufficient physical activity (1-299 minutes/week) did not increase the OR of common mental disorders. Practicing physical activity during leisure time, regardless of duration and weekly frequency, reduced the chances of common mental disorders in this population by 26%. CONCLUSIONS: Physical inactivity during leisure and school time is associated with the presence of common mental disorders in adolescence. The results suggest that sports practice, school physical education and physical activity during leisure time, even without reaching the current recommendation, are related to the mental health of young people.